2021
DOI: 10.1097/ccm.0000000000005209
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic and Hemorrhagic Stroke Among Critically Ill Patients With Coronavirus Disease 2019: An International Multicenter Coronavirus Disease 2019 Critical Care Consortium Study*

Abstract: OBJECTIVES: Stroke has been reported in observational series as a frequent complication of coronavirus disease 2019, but more information is needed regarding stroke prevalence and outcomes. We explored the prevalence and outcomes of acute stroke in an international cohort of patients with coronavirus disease 2019 who required ICU admission. DESIGN: Retrospective analysis of prospectively collected database. SETTING: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
0
19
1
1
Order By: Relevance
“…A total of 36 articles were included in the pooled analysis ( Table 1 ). 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 The majority (28; 78%) consisted of retrospective cohort studies whereas three (8%) were RCTs and five (14%) were prospective cohort studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 36 articles were included in the pooled analysis ( Table 1 ). 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 The majority (28; 78%) consisted of retrospective cohort studies whereas three (8%) were RCTs and five (14%) were prospective cohort studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patients affected by COVID-19 are at high risk of neurological sequelae, both during hospital stay ( 43 , 44 ) and at long-term follow-up ( 45 ). In critically ill patients with COVID-19, one of the most frequently reported neurological complications was delirium, with a high prevalence of acute and prolonged brain dysfunction ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aphasia and hemiparesis were more common in ischemic stroke, whereas altered mental status and pupillary changes were more common in patients with hemorrhagic stroke 12 . An international study of 2699 critically ill patients with COVID-19 found that 2.2% developed strokes in the ICU, twice the frequency of acute stroke in more general cohorts of patients with COVID-19, supporting critical illness as a discrete risk factor for stroke 13,14 …”
Section: Neurologic Approach To Critically Ill Patientsmentioning
confidence: 99%